RASIO SEKS DAN SEBARAN SPASIAL POPULASI GAJAH SUMATERA (Elephas maximus sumatranus) DI TAMAN NASIONAL TESSO NILO, RIAU - Nico Herlambang; Haris Gunawan; Herawati Sudoyo (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
The Sumatran Elephant (Elephas maximus sumatranus) is one of the largest mammal and endemic species on the island of Sumatra. It’s conservation status is critically endangered. The information about sex ratio and spatial distribution is an important component to make a priority in conservation strategy. The aims of this study were to determine sex ratio and spatial distribution of Sumatran Elephant in Tesso Nilo National Park. The multiplex PCR method was used in this study to amplify fragments SRY1 and AMELY2 on the Y chromosome and fragment PLP1 on the X chromosome for sex identification in Sumatran Elephant. The analysis of spatial distribution were conducted using Arc GIS 10.1. The result indicated that sex ratio of Sumatran Elephant population in TNNP is 1:3 and the distribution of Sumatran Elephant is generally spread outside of the region TNNP.